2012
DOI: 10.1080/00140139.2012.718802
|View full text |Cite
|
Sign up to set email alerts
|

Railway-controller-perceived mental work load, cognitive failure and risky commuting

Abstract: Commuting accidents occur frequently and at high cost. This study shows that mental work demands of railway staff are related to cognitive failure and risky commuting behaviour such as failing to give way and overlooking stop signs. Primary prevention of commuting accidents should include reduction of mental workload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 50 publications
0
22
1
1
Order By: Relevance
“…Presently it is unclear whether the observed associations are causal and, if so, whether the associations are directly due to exposure to SMF or are indirectly by means of other effects such as increased fatigue, disturbed quality of sleep, affected balance, or decreased concentration. Studies on work‐related fatigue have suggested an increased risk of accidents during commute after work , which is not congruent with our findings. Our results may be indicative of a delayed effect through, as of yet, unknown pathways.…”
Section: Discussioncontrasting
confidence: 99%
“…Presently it is unclear whether the observed associations are causal and, if so, whether the associations are directly due to exposure to SMF or are indirectly by means of other effects such as increased fatigue, disturbed quality of sleep, affected balance, or decreased concentration. Studies on work‐related fatigue have suggested an increased risk of accidents during commute after work , which is not congruent with our findings. Our results may be indicative of a delayed effect through, as of yet, unknown pathways.…”
Section: Discussioncontrasting
confidence: 99%
“…Cognitive failure during morning work was assessed at noon with the workplace cognitive failure scale [10]. The scale is regarded as a proxy for the accident risk [10][11][12] and consists of fifteen items addressing memory (e.g. "Cannot remember whether you have or have not turned off work equipment"), attention (e.g., "Do not fully listen to instructions") and action (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Many errors at work occur during routine task fulfillment and point to attentional slips or loss of working memory contents [10]. Such workplace cognitive failure has been consistently shown to be an antecedent of near accidents during the commute to work and back home [11,12] and to predict minor injuries at work [13], during sports after work [14] and domestic falls [15]. Hence, we hypothesised more frequent workplace cognitive failure on Monday morning compared to the subsequent working weekdays (Monday Effect; hypothesis 1 (H1)).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, although time pressured drivers admit to a variety of risky behaviours, they are less likely to believe that they will be ticketed for speeding (Beck, Wang, & Yan, 2012). Besides, it has been shown that cognitive failure significantly mediates the influence of work-related time pressure on near-accidents (Elfering, Grebner, & Haller, 2012). In light of the strong link between driving for work and the experience of time pressure while driving (Coeugnet et al, submitted for publication;McKenna, 2008), it seems likely that risky behaviours result from an excessive work-related attentional focus, but also from the importance of work-related goals.…”
Section: Time Pressurementioning
confidence: 96%